PENGUATAN KELUARGA DAN ORANG TUA ASUH PADA KOMUNITAS LEMBAGA HARAPAN UMMAT KECAMATAN LOWOKWARU MALANG - Fadloli Fadloli; Abdul Chalim; Widaningsih Widaningsih; Ahmad Bahauddin Almu’faro; Mohamad Sinal (Jurnal Pengabdian kepada Masyarakat, 2021)
Harum Institution is a social institution that is engaged in elevating the dignity of marginalized communities in the city of Malang. The purpose of this service activity is to provide spiritual strengthening for families and foster parents who are members of the Harapan Ummat Malang institutional community. The method of this activity is observation, interviews and about motivation and management of strengthening families and foster parents as well as interactive dialogue to provide solutions to family problems and successful parenting. The results of this of this service activity provide spiritual services in the form of tausiah and enlightenment and motivation to strengthen families and foster parents at the Harapan ummat Institution. Provide material about future family management in facing challenges, moral decline and difficulties in the economic field, towards a successful family in the hereafter.